Performance and FMECA of a wind turbine based on SCADA and lidar data - A. Bennouk; A. Nejmi; M. Ramzi (Institute of Advanced Engineering and Science, 2019)
This paper presents an approach to identify risks for different failures that could affect wind turbine performance, and reduce the measured annual electrical production (MAEP). The proposed approach is based on FMECA (failure mode, effects and criticality analysis) and wind turbine performance study. We present firstly the methodology of performance calculation based on IEC 61400 standard, then we identify the energy gap between the MAEP and WAEP for the case study, we present an extended and reviewed FMECA, by introducing definition of factors related to environment, health and security. As a result we present an actions plan for similar failures deduced from wind performance study and risk-based FMECA, in order to reduce failure risks and optimize production by consequence. The case study is a 2.3 MW onshore wind turbine, different data that are used in this paper were collected from SCADA and lidar.